Sport-specific warm-up attenuates static stretching- induced negative effects on vertical jump but not neuromuscular excitability in basketball players - Stevanovic, V. B.; Jelic, M. B.; Milanovic, S. D.; Filipovic, S. R.; Mikic, M. J.; Stojanovic, M. D. M. (Journal of Sports Science & Medicine, 2019)
The purpose of this study was to examine the acute effects of static stretching (SS) and dynamic stretching (DS), alone and in combination with specific basketball warm-up (SBWU), on the neuromuscular excitability and vertical jump height in basketball players. Twelve healthy young male basketball players participated in the study (18 ± 0.42 years; 17.4 - 18.6 age range; 188 ± 9 cm; 76.5 ± 9 kg). All participants completed two different stretching treatments (static and dynamic), performed on different days at least seven days apart, in the same period of training microcycle, in a counterbalanced order. Each session consisted of a self-paced jogging warm-up, followed by a 10-minute testing period (T0), which involved eliciting H reflex and M waves, followed by three trials of a vertical jump test. Participants then performed one of the treatment protocols. After another test (T1), participants conducted 8-minute specific basketball warm-up and then one more test (T2). Combined 3 (time) x 2 (stretching protocol) analysis of variance with repeated measures on both factors revealed that SS significantly decreased spinal excitability (H/M ratio) (p = 0.015, d = -0.38, percentage of change = -20.55%) and vertical jump height (p = 0.007, d = -1.91, percentage of change = -2.6%), but after SBWU, vertical jump height increased (p = 0.006, d = 1.13, percentage of change = 3.01%), while H/M ratio continued decreasing (p = 0.019, d = -0.45, percentage of change = -30.23%). Acute effects of DS, alone and in combination with SBWU were not significant. It seems that SBWU attenuates negative acute effects of SS on vertical jump performance in young basketball players, while DS appears to cause no signi?cant acute effect for this population.